Clinical impact of diabetes mellitus in patients undergoing transcatheter aortic valve replacement. Issue 1 (December 2015) - Berkovitch, Anat; Segev, Amit; Barbash, Israel; Grossman, Yoni; Maor, Elad; Erez, Aharon; Regev, Ehud; Fink, Noam; Mazin, Israel; Hamdan, Ashraf; Goldenberg, Ilan; Hay, Ilan; et al.
Abstract Background Diabetes mellitus (DM) and aortic stenosis (AS) are frequent findings in the elderly population. Data regarding the influence of DM on the outcomes of patients undergoing transcatheter aortic valve replacement (TAVR) due to AS are limited. The aim of this study was to examine the impact of DM on TAVR outcomes. Methods We investigated 443 patients with severe AS undergoing TAVR. Subjects were divided into insulin-dependent diabetic mellitus (IDDM) patients (N = 44), non-dependent insulin diabetic mellitus (NIDDM) patients (N = 114) and non-diabetics (N = 285) of whom 31 (74 %), 86 (79 %) and 209 (76 %) respectively had trans-femoral TAVR. Peri-procedural complications and outcomes were recorded according to the Valve Academic Research Consortium-2 criteria. Results Patients with IDDM as well as NIDDM demonstrated similar complication rates compared with non-diabetic patients, except for acute kidney injury (AKI) grade 3 [4 (2 %) and 3 (3 %) vs. 1 (0.4 %) respectively, p = 0.032]. Kaplan–Meier survival analysis showed that DM, regardless of the type of treatment, was not associated with increased 2 years mortality (Log-rank p value 0.44). Multivariate cox regression analysis adjusted for age, gender, coronary artery disease, DM, AKI3, hypertension, chronic renal failure and peripheral vascular disease found that AKI3 was associated with increased risk of 2 years mortality [HR = 7.35, 95 % CI 2.16–25.07, p = 0.001] whereas female gender was found as a protective factor [HR = 0.47, 95 % CI 0.28–0.8, p = 0.005], and DM was not associated with increased risk. Conclusions Following TAVR, DM patients seem to have similar peri-procedural and mid-term outcomes compared with patients without DM, while IDDM patients seem to suffer greater incidence of AKI. Further research in larger cohorts of patients is needed to validate our results.